COVID-19 Pandemic on Fire: Evolved Propensities for Nocturnal Activities as a Liability Against Epidemiological Control - Varella, Marco Antonio Correa; Luoto, Severi; Soares, Rafael Bento da Silva; Valentova, Jaroslava Varella (Frontiers in Psychology, 2021)
Humans have been using fire for hundreds of millennia, creating an ancestral expansion towards the nocturnal niche. The new adaptive challenges faced at night were recurrent enough to amplify existing psychological variation in our species. However, under some circumstances, such as respiratory pandemics, the psychobehavioral traits favored by the nocturnal niche might be counter-productive, increasing contagion rates of a disease that can evade the behavioral immune system for being pre/asymptomatic. Night-time is dangerous, so it selects for individuals with higher tendencies for paranoia, risk-taking, and sociability (because of security in numbers). During night-time, individuals are generally tired and show decreased self-control and increased impulsive behaviors. The lower night-time visibility favors concealment of identity and opens opportunities for disinhibition of self-interested behaviors. Individuals with an evening-oriented chronotype are more paranoid, risk-taking, extraverted, impulsive, promiscuous, and antisocial. The eveningness epidemiological liability hypothesis presented here suggests that during the COVID-19 pandemic, the evening-oriented psychobehavioral profile can have collectively harmful consequences: there is a clash of core tendencies between the nocturnal chronotype and the recent viral transmission-mitigating safety rules. The pandemic safety protocols disrupt normal social activity, particularly at night when making new social contacts is desired. The SARS-CoV-2 virus is contagious even in pre/asymptomatic individuals, which enables it to mostly evade our evolved contagious disease avoidance mechanisms. A growing body of research has indirectly shown that individual traits interfering with social distancing and anti-contagion measures are related to those of the nocturnal chronotype. Indeed, some of the social contexts that have been identified as superspreading events occur at night, such as in restaurants, bars, and nightclubs. Furthermore, nocturnal environmental conditions favor the survival of the SARS-CoV-2 virus much longer than daytime conditions. We compare the eveningness epidemiological liability hypothesis with other factors related to non-compliance with pro-health protocols: sex, age, and life-history. Although there is no direct link between the nocturnal chronotype and non-compliance with pandemic safety protocols yet, security measures and future empirical research should take this crucial evolutionary mismatch into account, and focus on how to avoid nocturnal individuals becoming superspreaders, offering secure alternatives for nocturnal social activities.